Berry antioxidants: small fruits providing large benefits - Manganaris, George A. (2014)
Small berry fruits are consumed because of their attractive colour and special taste, and are considered one of the richest sourcesof natural antioxidants. Their consumption has been linked to the prevention of some chronic and degenerative diseases. Theterm ‘berry fruits’ encompasses the so-called ‘soft fruits’, primarily strawberry, currants, gooseberry, blackberry, raspberry,blueberry and cranberry. The objective of this review is to highlight the nutraceutical value of berries and to summarize thefactors affecting berry fruit antioxidants. Particular attention is given to postharvest and processing operation factors thatmay affect fruit phytochemical content. The structure–antioxidant relationships for phenolic compounds – the main group ofantioxidants in this fruit group – are presented and major areas for future research are identified.